Program Aplikasi Tata Kelola Perpustakaan Program Studi Sistem Komputer Universitas Surakarta Berbasis Visual Basic 6.0 - Taruna Perkasa; Cicilia Puji Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
At the University of Surakarta , especially in Computer Systems Studies Program , there have their own library . Nevertheless , the books contained in the library , yet can be used by students of Computer Systems . This is because there is no system to regulate the governance of the library . Based on these problems , the researchers were motivated to create a library of application program is implemented by the library for Computer System Studies Program University of Surakarta. In making the application program this library , before making the database . Researchers collecting data first. When the necessary data has been collected, and researcher to design and manufacture a database . Databases created using MySQL . Then create a library of application program using Visual Basic 6.0 . After that create a report using Crystal Report 8.5 . When making the application program has been completed, a periodic testing program to detect if an error in the program. Implement a computerized system in the library of the University of Surakarta Computer Systems can ease the workload of the librarian. Besides process transactions, borrowing , repayment transaction and the book search can be done more easily and more quickly .